Plan zonal El Campestre, proyectando Ibagué hacia un desarrollo urbano sostenible (2021)
Cities are the territories with the highest concentration of wealth, amidst great economic, environmental, political and cultural diversity. But at the city level, there do not seem to be carefully defined planning strategies in the medium and long term, which brings with it the settlement of millions of families in highly vulnerable areas, amid increasing privatization of public space, depredation of the environment environment and planetary territory in general